2017
DOI: 10.1097/bot.0000000000000748
|View full text |Cite
|
Sign up to set email alerts
|

Local Zinc Chloride Release From a Calcium Sulfate Carrier Enhances Fracture Healing

Abstract: The effective dose of ZnCl2 augmentation for the enhancement of fracture healing in rats was reduced 3-fold in this study compared with previous findings. Furthermore, CaSO4 acted synergistically with ZnCl2 to increase the mechanical strength and stability at the fracture site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…29 Krell et al ., using a calcium sulfate paste as a carrier, found that an intramedullary dose of 1 mg/kg ZnCl 2 (ZnCl 2 to body weight) significantly improved rat femur fracture healing as compared to a 3 mg/kg dose of ZnCl 2 . 15…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Krell et al ., using a calcium sulfate paste as a carrier, found that an intramedullary dose of 1 mg/kg ZnCl 2 (ZnCl 2 to body weight) significantly improved rat femur fracture healing as compared to a 3 mg/kg dose of ZnCl 2 . 15…”
Section: Discussionmentioning
confidence: 99%
“…In prior work, we demonstrated that zinc salts and other insulin-mimetic metal salts can promote bone regeneration in rats. 15,16 Therefore, we hypothesized that zinc could be a possible osteogenic adjuvant for bone allograft. 17 We tested this hypothesis by adding different zinc salts to commonly used DBM and cancellous bone chip allograft and evaluated the zinc-allograft for osteogenic activity in a rat femoral defect model.…”
Section: Introductionmentioning
confidence: 99%
“…What is more, Zn shows antibacterial and anti-inflammatory properties and inhibits osteoclasts differentiation [ 40 ]. Other authors have reported a positive influence of Zn on bone fracture healing [ 41 ]. The incorporation of zinc in various calcium phosphate-based biomaterials for bone regeneration led to higher new bone formation and bone–implant contact in vivo [ 42 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral intake of Zn can increase serum Zn and alkaline phosphatase (ALP) activity and promote fracture healing in patients [ 200 ]. Local injection of ZnCl 2 promoted fracture healing of bones in rats, and increased the mechanical strength and stability after fracture healing [ 201 , 202 ].…”
Section: Mg-based Bms For Oral and Maxillofacial Applicationmentioning
confidence: 99%
“…Zn has a well-known insulin-mimetic property, which is conducive to cartilage regeneration [ 293 ]. Local application of ZnCl 2 enhanced cartilage formation and improved endochondral ossification [ 201 , 202 ]. In vitro experiments showed that a low concentration of Zn ions could increase the proliferation rate of growth plate chondrocytes by 40–50% and increased the synthesis of highly charged proteoglycan molecules, thus reducing mineralization [ 294 ].…”
Section: Perspectivesmentioning
confidence: 99%